A Domino Reaction for the Synthesis of Novel 1,3-Dihydrofuro[3,4-c]pyridines from Pyridoxal and Ketones - Casadia, Izamara; Daher, Thalita O.; Moura, Sidnei; Back, Davi F.; Faoro, Eliandro; Schwalm, Cristiane S.; Casagrande, Gleison A.; Paveglio, Guilherme C.; Pizzuti, Lucas (Synthesis, 2021)
A convenient domino route for the synthesis of novel 1,3-dihydrofuro[3,4-c]pyridines from pyridoxal and alkyl, aryl or heteroaryl ketones under basic conditions is reported. A series of nine derivatives is obtained in 53–90% yields after stirring reactants for 48 hours at room temperature. Most products are easily isolated by filtration followed by recrystallization from ethanol. All products were fully characterized by FTIR, HRMS, and 1H and 13C NMR spectroscopy. The X-ray crystal structure of a representative example of the 1,3-dihydrofuro[3,4-c]pyridine series is also presented.
Keywords: biobased molecules; Claisen–Schmidt condensation; domino reactions; fused-ring systems; oxa-Michael addition; vitamins